Geothermal resource potentials estimation from the interpretation of aeromagnetic data over parts of Southwestern Nigeria (African Scientific Reports, 2024)
In a bid to explore unconventional electricity generation sources and reduce effects of fossil fuels, this study evaluates geothermal resource potentials over parts of Southwestern Nigeria, precisely depth to the bottom of magnetic source (DBMS), heat flow, geothermal gradient and their relationships. Regional-residual anomaly separation was conducted, and spectral analysis was applied on the residual anomaly component of 14 aeromagnetic data sheets. Depth to the bottom of magnetic source varies between 1.87 and 6.26 km, with average value of 3.50 km, heat flow varies between 23.18 and 77.38 mWm−2, with average value of 43.79 mWm−2, while geothermal gradient varies between 9.27 and 30.95 oC/km with average value of 17.52 oC/km. Northcentral region has the highest heat flow (77.4 mWm−2), followed by Northeast (68.3 mWm−2), Southwest has the least (< 40.0 mWm−2) while Southeast has values in between the extremes. A comparison between the average heat flow and that of ‘thermally stable’ continental regions of the world (60 or 65) mW/m2 gives 72.98 or 67.37% respectively. The estimated heat is probably from mantle plumes, radioactive sources or heat generated from pressures within basements that are overlaid by thick thermally insulated sediments, hence hot magmatic fluid flows into fractured basement and cause hydrothermal alterations of surrounding rocks. Since most geodynamic operations depends on thermal structure of the earth’s crust, the result of this study has undoubtedly contributed significantly to the body of existing thermal knowledge and closed the information gap regarding crustal temperature distribution at depth in Southwest part of Nigeria and Nigeria in general.
Keywords: Aeromagnetic, Magnetic-source-depth, Thermal gradient, Heat flow, Geothermal